PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS WEBSITE NEARPOD PADA MATA PELAJARAN IPAS KELAS V MATERI SISTEM ORGAN TUBUH MANUSIA - Devi Aulia Ulva; Destrinelli; Suci Hayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by the lack of use of technology-based interactive multimedia in science and science learning in class V at SDN 34/I Teratai. The research was conducted at SDN 34/I Teratai. This research aims to produce interactive multimedia that is valid and practical for teachers to use in science and science learning. The product is nearpod-based interactive multimedia in class V science and science subjects, material on human body organ systems. This type of research is Research and Development with the ADDIE Lee & Owens development model. The data in this research is qualitative and quantitative data. Qualitative data was obtained from interviews, suggestions and input from validators. Meanwhile, quantitative data was obtained from the results of filling out questionnaires from validation experts and practitioners. Language validation obtained an average score of 4.7 which is in the very valid category. Media validation obtained an average score of 4.8, which is in the very valid category. Material validation received an average score of 4.7 in the very valid category. The expert practitioner assessment obtained an average score of 4.93 with very practical conclusions. And the student response questionnaire obtained an average score of 4.8 and was in the very practical category.  Based on the data obtained, it was concluded that the nearpod interactive multimedia in the class V science course material on human body organ systems that was developed was declared valid and practical to use.   Keywords: IPAS, interactive multimedia, nearpod